Dentinal hypersensitivity following scaling and root planing: comparison of low-level laser and topical fluoride treatment - Pesevska S; Nakova M; Ivanovski K; Angelov N; Kesic Lj; Obradovic R; Mindova S; Nares S (Springer Science and Business Media LLC, 2010)
The aim of this study is to compare the effectiveness of low-level laser irradiation to traditional topical fluoride treatment for treatment choices of dentinal hypersensitivity following scaling and root planing. The experimental group (15 patients) was treated with low-energy-level diode laser at each site of dentinal hypersensitivity following scaling and root planning. The control group (15 patients) received topical fluoride treatment (protective varnish for desensitization). All the patients were treated at baseline visit, and then at day 2 and 4 after the initial treatment; the pain was subjectively assessed by the patients as strong, medium, medium low, low, or no pain. Total absence of the dental hypersensitivity was reported in 26.66% of the examined group even after the second visit, compared to the control group where complete resolution of the hypersensitivity was not present after the second visit in any of the treated cases. Complete absence of pain was achieved in 86.6% of patients treated with laser and only in 26.6% in the fluoride treated group, after the third visit. Based on our findings, we conclude that low-energy biostimulative laser treatment can be successfully used for treatment of dental hypersensitivity following scaling and root planing.